Comparative corporate governance of non-profit organizations / edited by Klaus J. Hopt and Thomas Von Hippel. - Hopt, Klaus J., 1940-; Hippel, Thomas von, 1972- (International corporate law and financial market regulation., 2010)
The economic importance of the non-profit sector is growing rapidly in the USA and Europe. However, the law has not kept abreast with its development. The European Court of Justice has extended certain freedoms of the EC Treaty to non-profit organisations, and more case law is expected to follow in the near future, but the observations, theories, solutions and legal and non-legal rules in this field are manifold. The chances of harmonising the law on a European level are slim. Despite these differences, a common core of international corporate governance problems and regulatory solutions can be seen. This volume of essays brings together a variety of international experts from both corporate governance and governance of non-profit organisations to compare the two areas and explore the lessons that can be learned regarding comparative corporate governance for non-profit organisations.